PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizka Yulia Putri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to examine the partial and simultaneous effects of asset structure, firm size and profitability on debt policy. Where independent variable in this research is asset structure, company size and profitability, while dependent variable is debt policy. The sample that has been used is secondary data derived from the financial statements of pulp and paper companies listed on the Indonesia Stock Exchange. Sampling method used purposive sampling. The sample used is 6 companies. Data analysis techniques used are simple linear regression and multiple linear regression. The result of research partially show that asset structure has negative significant effect to debt policy, firm size have positive and significant influence to debt policy and profitability has negative significant effect to debt policy. While simultaneously asset structure, firm size and profitability have positive and significant influence to debt policy.Key Words : asset structure, firm size, profitability, debt policy